A definition of global oral health: An expert consensus approach by the Consortium of Universities for Global Health's Global Oral Health Interest Group. Issue 1 (31st December 2020) - Seymour, Brittany; James, Zak; Shroff Karhade, Deepti; Barrow, Jane; Pruneddu, Alessio; Anderson, Nina Kay; Mossey, Peter; Definition of Global Health, Task Force for the
ABSTRACT: Definitions can generate actionable consensus for a given subject matter by resolving important differences in philosophy and best practices and by streamlining activities for a stronger strategic direction. Interest in the global dimensions of oral health, a generally neglected area of global health, is growing; yet, no previously published research has defined the term 'global oral health.' As such, the Global Oral Health Interest Group of the Consortium of Universities for Global Health determined a need for an introductory definition of 'global oral health' to guide program planning, implementation, and evaluation. With the oversight of an expert senior Task Force for the Definition of Global Oral Health, we employed a mixed-methods approach using the more common expert consensus-building Delphi technique combined with the lesser utilized Q methodology. This approach allowed us to identify the interconnectedness of global oral health themes and integrate multiple, seemingly disparate, topics into a single streamlined concept. Our resulting definition is as follows: Global Oral Health aims for optimal oral health for all people and elimination of global health inequities through health promotion, disease prevention, and appropriate oral care approaches that consider common determinants and solutions and acknowledge oral health as part of overall health . The purpose of this short communication is to generate a narrative around our proposed definition of global oral health to support establishing guidelines and developing best practices for academic global oral health programs, policies, and practices that aim to achieve a goal of oral health globally.